Relationship between human resource management practices and organizational performance: the moderating role of interfirm collaboration and environment of Malaysian Research and Development (R&D) organizations / Zurina Adnan - Adnan, Zurina (2013)
Since 1996, the Research and Development (R&D) sector in Malaysia has received greater policy attention than before. Despite fiscal and non-fiscal incentives provided to support the growth of this sector, the level of R&D measured in terms of R&D outputs (i.e. number of patent) is still dismal which is mirrored in the overall performance of local R&D companies. Many studies have investigated factors which influence the performance of organizations. The present study attempts to examine the relationship between human resource management (HRM) practices and organizational performance of R&D firms based on contingency theory and resource based view. The moderating role of interfirm collaboration and environment on the relationship between HRM practices and organizational performance are also studied. Organizational performance was measured in terms of profitability. The data for the study were obtained from survey responses from 64 R&D companies. Results of EFA and CFA confirmed the 4 dimensions of HRM practices: participation, reward, training and development, and teamwork practices. Regression results showed participation and reward practices have positive and significant relation with organizational performance while training and development practice has negative relation with organizational performance. There is no significant relationship between teamwork practice and organizational performance. Results also indicated that only collaboration in manufacturing significantly moderated the relationship between some of the HRM practices and organizational performance. Other types of interfirm collaborations did not show any moderating roles on the aforesaid relationships. Also, the present study found that environment was not a moderator in the relationship between HRM practices and organizational performance. Overall, the findings of the present study provide partial support of Contingency Theory and RBV. Theoretical contributions and managerial implications of the study as well as suggestions for future research were discussed.